Development of Evaluation Devices Producing Short Story Text with Rebecca M. Valette’s Taxonomy and CLIL Approach to XIth Grade Senior High School Students - Leksono, M. Lukman; Subyantoro, Subyantoro (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The objectives of this research are (1) to describe the development characteristics of short story text evaluation tools of XIth grade Senior High School class participants by using Rebecca M. Valette taxonomy and CLIL approach based on teacher perception, (2) to describe the development of short story text evaluation tool for XIth grade Senior High School students using Rebecca M. Valette’s taxonomy and CLIL approach. (3) to describe the validity and reliability  prototypes of short story text evaluation tools for XIth grade Senior High School class participants using Rebecca M. Valette’s taxonomy and CLIL approach. The design of this research is R & D (Reseach and Development) approach with research step those are (1) phase I (preliminary study and early development, (2) stage II (development), (3) Stage III (Testing and Validation). This includes the data needs of evaluation tool development according to teacher's perception, data of expert evaluation result, and limited test data in the score form. The sample of this research is evaluation tool produce short story text on XIth grade Senior High School students. Research results are (1) development characteristic of short story text evaluation tool on XIth grade Senior High School students using Rebecca M. Valette’s taxonomy and CLIL approach based on teacher’s perceptions, (2) development of short story text evaluation tools for XIth grade Senior High School students using taxonomy Rebecca M. Valette’s and CLIL approach, (3) validity and the prototype reliability of short story text evaluation tools for XIth grade Senior High School students using Rebecca M. Valette’s taxonomy and CLIL approach.